Diabetic nephropathy is an independent factor associated to severe subclinical atheromatous disease. Issue 1 (September 2015) - Barrios, Clara; Pascual, Julio; Otero, Sol; Soler, Maria J.; Rodríguez, Eva; Collado, Silvia; Faura, Anna; Mojal, Sergi; Navarro-González, Juan F.; Betriu, Angels; Fernandez, Elvira; Valdivielso, Jose M.; et al.
Abstract: Background: Atheromatous disease (AD) is a risk factor for death in renal patients. Traditional CV risk factors do not predict the presence of AD in this population. The aim of this study is to analyze whether the etiology of the primary renal disease influences in the risk of having silent AD. Study design: Observational cross-sectional study in chronic kidney disease patients without previous cardiovascular events. Settings and Participants: 2436 CKD subjects without any previous CV event included in the prospective Spanish multicenter NEFRONA study. Patients were classified according to primary renal disease: diabetic nephropathy (n = 347), vascular nephropathy (n = 476), systemic/glomerular disease (n = 447), tubulointerstitial and drug toxicity nephropathy (n = 320), polycystic kidney disease (n = 238), non-filiated nephropathy (n = 406) and other causes (n = 202). Predictors: B-mode and Doppler ultrasonography analysis of the carotid arteries were performed to measure intima media thickness (IMT) and the presence of plaques. Clinical and laboratory parameters related to CV risk were also determined. Outcomes: AD was scored according with the ultrasonography findings and the ankle-brachial index into two large groups: absence or incipient AD and severe AD. Results: In multivariate regression analysis, older age (OR 1.09/year [1.088–1.108]), smoking habit (OR 2.10 [1.61–2.74]), male gender (OR 1.33 [1.09–1.64]), grade-5D of CKD (OR 2.19 [1.74–2.74]), and diabetic nephropathy (OR 2.59 [1.93–3.48]) are independent risk factors for severe AD. The prevalence of silent AD was highest for diabetic nephropathy with grade-5D of CKD (82.2%) and lowest with stages 2–3 CKD systemic/glomerular disease (36.6%). Limitations: Observational study with the potential for confounding. Conclusion: In CKD patients without any CV event in the background clinical history, diabetic nephropathy as primary renal disease is the most significant factor associated to severe silent AD. Furthermore, this difference was independent of other conventional risk factors for atherosclerosis and CV events.